2019
DOI: 10.4314/jasem.v23i9.19
|View full text |Cite
|
Sign up to set email alerts
|

Review on Solid Waste Generation and Management in Sub-Saharan Africa: A Case Study of Nigeria

Abstract: Nigeria just likes every other country in sub-Sahara Africa is faced with solid waste generation and management. Solid waste is dump indiscriminately and seen in huge heaps on any piece of unused land, around buildings, drainage system, institutions, playing ground, roads side, and in the open market places in major cities and towns. Living with solid wastes littered around seems to be an acceptable way of life among the people in this part of the world. This research work reported intensive review on solid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Although the PSP ranking is the highest, none of the service providers did well enough to be classified as delivering efficient and effective solid waste management suggesting that there is much to be done. The above finding is similar to the submissions by Choi (2016) and Orhorhoro and Oghoghorie (2019).…”
Section: Resultssupporting
confidence: 91%
“…Although the PSP ranking is the highest, none of the service providers did well enough to be classified as delivering efficient and effective solid waste management suggesting that there is much to be done. The above finding is similar to the submissions by Choi (2016) and Orhorhoro and Oghoghorie (2019).…”
Section: Resultssupporting
confidence: 91%
“…According to the experts of Addis Ababa Solid Waste Management Agency, in the city, the formal waste management sector is characterized by the primary collection, carried out mainly by pre-collector associations, the secondary collection, and final disposal, mostly carried out by the government, and few SMEs. Similarly, a study conducted in Bangladesh [39], Mozambique [40], and Nigeria [41] showed that, like most developing According to the experts of Addis Ababa Solid Waste Management Agency, in the city, the formal waste management sector is characterized by the primary collection, carried out mainly by pre-collector associations, the secondary collection, and final disposal, mostly carried out by the government, and few SMEs. Similarly, a study conducted in Bangladesh [39], Mozambique [40], and Nigeria [41] showed that, like most developing countries, waste is collected from generation sources, and transferred to ultimate disposal sites (landfill).…”
Section: Collection Solid Waste At Addis Ababamentioning
confidence: 99%
“…Similarly, in developing countries, cities have failed to fully implement the ISWM strategies at their full capacity. However, in the major cities, developing literature shows there has been an attempt, but rapid urbanization, population growth, increasing consumption, and way of life makes the application of ISWM difficult [11,[40][41][42].…”
Section: Collection Solid Waste At Addis Ababamentioning
confidence: 99%
“…Poor planning of cities, population inflation, expansion of urban areas, higher living standards among others results in improper waste management in most low-income countries (Al-Salem et al, 2018;Ghinea et al, 2016); resulting in degradation of the earth's resources and quality of life (Carota et al, 2018). In the recent world, 1.3 billion tonnes of solid waste are produced yearly (Orhorhoro & Oghoghorie, 2019), with the expectation of 2.2 billion tonnes by 2025 (Kharlamova et al, 2016). In African countries, about 95% of solid waste produced from different sources is discarded at peripheries of cities or in open dumpsites and wetland areas (Weldeyohanis et al, 2020).…”
Section: Solid Waste Management Practices Worldwidementioning
confidence: 99%